Silk protein dry powder particles and preparation method thereof

By preparing silk protein dry powder particles, the problems of regulating the spatial structure and crystallinity of silk fibroprotein in the prior art were solved, and high density, high mechanical strength and biocompatible silk protein microparticles were achieved, which were suitable for tissue engineering and biomedicine fields.

CN119899402APending Publication Date: 2025-04-29NANJING XINSIRONG BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510085258.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The prior art is difficult to effectively regulate the spatial structure and crystallinity of silk fibroin, resulting in limited application of its tissue engineering.

Method used

By preparing silk protein dry powder particles, including preparing silk fibroin lyophilized foam, dissolving in hexafluoroisopropanol solution, forming a gel and removing hexafluoroisopropanol, crushing into an emulsion and lyophilizing, obtaining silk protein dry powder particles with a density greater than water.

Benefits of technology

The preparation of high-density silk protein microparticles is realized, which enhances the mechanical strength of the material, extends the in vivo degradation cycle, reduces the cost of use, and improves the biocompatibility and safety of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899402A_ABST
    Figure CN119899402A_ABST
Patent Text Reader

Abstract

The invention discloses a silk protein dry powder particle and a preparation method thereof.The preparation method comprises the steps that silk fibroin freeze-dried foam is prepared from silk formed by degumming silkworm cocoons, the degumming time is 10-60 minutes, the silk fibroin freeze-dried foam is dissolved with a hexafluoroisopropanol solution to generate a first solution, and in the first solution, the silk fibroin freeze-dried foam is prepared from silk obtained by degumming silkworm cocoons; the concentration of the silk fibroin is 20%-30%, mixing the first solution and pure water according to a first proportion, standing for a first time to form first silk fibroin gel, and removing hexafluoroisopropanol in the first silk fibroin gel by using a deionized solution to obtain second silk fibroin gel, and crushing the second silk fibroin gel into a silk fibroin emulsion by using water, and freeze-drying the silk fibroin emulsion to obtain silk fibroin dry powder particles. According to the invention, high-density fibroin microparticles can be obtained, and when powder of particles with the same size is used as a filler, the degradation time period in vivo can be longer, so that the use cost can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of material technology, and in particular to a silk protein dry powder particle and a preparation method thereof. Background Art

[0002] Silk protein is mainly composed of fibroin and sericin. As the core structural protein, fibroin accounts for 70-80% of the silk protein content. As a natural protein, fibroin has been found to have good biocompatibility, bioabsorbability, and biodegradability, and has great application potential in tissue engineering. By envisioning the potential applications of silk fibroin, researchers have processed silk fibroin into films, microparticles, nanospheres, nanofiber matrices, adhesives, gels, etc., but most of the current processing methods cannot meet the needs of practical applications. For example, the gel directly processed from silk fibroin has the characteristics of being brittle and hard, and has a small elastic modulus, and cannot be directly applied to tissue engineering.

[0003] Therefore, a new method is needed to regulate the spatial structure and crystallinity of silk fibroin so that it can be truly applied. Summary of the invention

[0004] The present application provides a silk protein dry powder particle and a preparation method thereof, which is used to reduce or even eliminate the introduction of bubbles in the droplet generation process so as to facilitate the smooth progress of the subsequent amplification reaction.

[0005] On the one hand, the present application provides a method for preparing silk protein dry powder particles, comprising:

[0006] Preparation of freeze-dried silk fibroin foam; the freeze-dried silk fibroin foam is obtained by degumming silk from silkworm cocoons; the degumming time is 10 minutes to 60 minutes;

[0007] Dissolving the freeze-dried silk fibroin foam with a hexafluoroisopropanol solution to generate a first solution; in the first solution, the concentration of the silk fibroin is 20%-30%;

[0008] Mixing the first solution and pure water in a first ratio and leaving them to stand for a first period of time to form a first silk fibroin gel;

[0009] placing the first silk fibroin gel in a deionized solution at a first temperature, and removing hexafluoroisopropanol in the first silk fibroin gel by using the deionized solution to obtain a second silk fibroin gel;

[0010] The second silk fibroin gel is broken into a silk fibroin emulsion by using water, and the silk fibroin emulsion is freeze-dried to obtain silk fibroin dry powder particles; the density of the silk fibroin dry powder particles is greater than the density of water.

[0011] In some possible embodiments, preparing the freeze-dried silk fibroin foam comprises:

[0012] preparing a silk fibroin aqueous solution;

[0013] Freeze the silk fibroin aqueous solution in an environment of -30°C to -5°C;

[0014] The frozen silk fibroin aqueous solution is placed in a freeze dryer for vacuum freezing to obtain a silk fibroin freeze-dried foam;

[0015] The vacuum freezing time is 5h to 8h, the vacuum freezing temperature is -20°C to -5°C, and the vacuum freezing pressure is 0.005mBar to 0.8mBar.

[0016] In some possible embodiments, preparing a silk fibroin aqueous solution comprises:

[0017] Weighing dry and clean silk cocoons, placing them in a sodium carbonate solution, and heating them to remove the sericin from the cocoons and perform degumming to form silk;

[0018] The silk is placed in ultrapure water and washed several times;

[0019] The washed silk is dried, and the dried silk is mixed with a lithium salt aqueous solution by stirring and evenly mixing, and the mixture is kept warm to obtain a silk fibroin lithium salt aqueous solution;

[0020] Pour the silk fibroin lithium salt aqueous solution into a dialysis bag and dialyze in ultrapure water;

[0021] The dialyzed silk fibroin lithium salt aqueous solution is transferred to a centrifuge tube, centrifuged, and the supernatant after centrifugation is collected to obtain the silk fibroin aqueous solution.

[0022] In some possible embodiments, the silk cocoon is a silk cocoon after the pupae are removed; the shape of the silk cocoon is rectangular or square, and the area of ​​the silk cocoon is 1 mm2 to 1000 mm2; the concentration of the sodium carbonate solution is 20 g / L to 80 g / L, and the volume ratio of the mass of the silk cocoon to the sodium carbonate solution is (1:2) g / L.

[0023] In some possible embodiments,

[0024] The sodium carbonate solution is heated by an electric furnace or a pressure cooker, the heating temperature is 60°C to 100°C, the heating pressure is 0.5MPa to 1MPa, and the average molecular weight of silk fibroin in silk is controlled by the heating time, and the average molecular weight of silk fibroin is 10KDa to 300KDa.

[0025] In some possible embodiments,

[0026] The silk is washed by stirring washing or static soaking, wherein the stirring method of stirring washing is mechanical stirring or magnetic stirring, and the magnetic stirring speed is 1r / min~2000r / min; in a single washing process, the mass ratio of silk to ultrapure water is 1:20~1:50, and the time is 60s~5h; after each washing, the silk is taken out and squeezed dry, and the washing is repeated 1 time to 50 times.

[0027] In some possible embodiments,

[0028] The drying method of the drying treatment is natural air drying or heating ventilation drying. The temperature of heating ventilation drying is 5°C to 100°C, and the drying time is 1h to 100h.

[0029] In some possible embodiments,

[0030] The lithium salt aqueous solution is lithium thiocyanate solution or lithium bromide solution, the concentration of the lithium salt aqueous solution is 0.01g / ml~2g / ml, the volume ratio of the mass of the dried silk to the lithium salt aqueous solution is (1~100):100g / ml; the insulation temperature is 30℃~50℃, and the insulation time is 0.5h~5h.

[0031] In some possible embodiments,

[0032] The specifications of the dialysis bag are 10Da~10000000Da, and the dialysis method is static dialysis or magnetic stirring dialysis; among them, the stirring speed of the magnetic stirring dialysis is 1r / min~2000r / min, the time interval for changing water during the dialysis process is 0.1h~100h, and the volume of ultrapure water required for each dialysis is 1mL~1000L.

[0033] In some possible embodiments,

[0034] The rotation speed of the centrifugal treatment is 10 r / min to 20000 r / min, the time is 6 s to 2 h, and the temperature is 1°C to 5°C.

[0035] In some possible embodiments,

[0036] The mass ratio of the lyophilized silk fibroin powder to the hexafluoroisopropanol solution is 1:(1-10), the dissolution temperature is 30-50°C, the dissolution time is 1-5h, and the container is sealed during the dissolution.

[0037] In some possible embodiments,

[0038] The first ratio is 5:(1~2); the first duration is 24h.

[0039] In some possible embodiments,

[0040] The first temperature is 30°C to 80°C, and the removal time is 3 to 7 days.

[0041] In some possible embodiments, after freeze-drying the silk fibroin emulsion to obtain silk fibroin dry powder particles, the method further comprises:

[0042] Screening the silk protein dry powder particles using a filter screen of a preset size to obtain silk protein dry powder particles less than or equal to the preset size;

[0043] The preset size is less than or equal to 100 microns.

[0044] In some possible embodiments, the density of the silk protein dry powder particles is 1.1 g / cm 3 .

[0045] On the other hand, a silk protein dry powder particle is provided, and the silk protein dry powder particle is prepared by the preparation method as described above.

[0046] The embodiment of the present application provides a silk fibroin dry powder particle and a preparation method thereof, the method comprising: preparing a silk fibroin freeze-dried foam, the silk fibroin freeze-dried foam being obtained by degumming silkworm cocoons for 10 minutes to 60 minutes, dissolving the silk fibroin freeze-dried foam with a hexafluoroisopropanol solution to generate a first solution, in which the concentration of the silk fibroin is 20% to 30%, mixing the first solution and pure water in a first ratio, and allowing the mixture to stand for a first time to form a first silk fibroin gel, placing the first silk fibroin gel in a deionized solution at a first temperature, removing the hexafluoroisopropanol in the first silk fibroin gel with the deionized solution to obtain a second silk fibroin gel, crushing the second silk fibroin gel into a silk fibroin emulsion with water, and freeze-drying the silk fibroin emulsion to obtain the silk fibroin dry powder particles, wherein the density of the silk fibroin dry powder particles is greater than the density of water. The present application controls the degumming time of silk fibroin and dissolves the freeze-dried silk fibroin foam by hexafluoroisopropanol to obtain a high concentration of hexafluoroisopropanol containing silk fibroin, thereby obtaining high-density silk fibroin microparticles (with a density greater than that of water and close to the density of silk fibroin hard bone nails). In this way, when powders of particles of the same size are used as fillers, the degradation period in the body can be longer, thereby reducing the cost of use. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0048] Figure 1This is a schematic diagram of the structure of a silk protein dry powder particle provided in an embodiment of the present application;

[0049] Figure 2 It is a schematic diagram of a process for preparing a freeze-dried silk fibroin foam provided in an embodiment of the present application;

[0050] Figure 3 It is a schematic flow chart of a method for preparing a silk fibroin aqueous solution provided in an embodiment of the present application;

[0051] Figure 4 It is a schematic flow chart of a method for preparing a first silk fibroin gel provided in an embodiment of the present application;

[0052] Figure 5 It is a density schematic diagram of a silk protein dry powder particle provided in an embodiment of the present application. DETAILED DESCRIPTION

[0053] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0054] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data sets used in this way can be interchanged where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product, or server that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products, or devices.

[0055] See also Figure 1 , Figure 1 : is a schematic flow chart of a method for preparing a silk protein dry powder particle provided in an embodiment of the present application, and the method may include the following steps:

[0056] In step S10, freeze-dried silk fibroin foam is prepared; the freeze-dried silk fibroin foam is obtained by degumming silk from silkworm cocoons; the degumming time is 10 minutes to 60 minutes.

[0057] In the embodiment of the present application, the lyophilized silk fibroin foam is obtained by degumming silk cocoons for a preset time. Optionally, the preset time is the degumming time, which can be between 10 minutes and 60 minutes, such as degumming for 10 minutes, 60 minutes, or 45 minutes. The specific degumming time can be adjusted according to the number of cocoons and the formation results.

[0058] See also Figure 2 , Figure 2 1 is a schematic flow chart of a method for preparing a freeze-dried silk fibroin foam provided in an embodiment of the present application. The method may include the following steps:

[0059] In step S101, a silk fibroin aqueous solution is prepared.

[0060] The following is a method for preparing a silk fibroin aqueous solution. Figure 3 , Figure 3 : is a schematic flow chart of a method for preparing a silk fibroin aqueous solution provided in an embodiment of the present application, and the method may include the following steps:

[0061] In step S1011, dry and clean silk cocoons are weighed and placed in a sodium carbonate solution for heating to remove sericin from the cocoons for degumming to form silk.

[0062] In the embodiment of the present application, in step S1011, a certain amount of dry clean cocoons can be weighed using a scale, and the weighed clean cocoons are placed in a sodium carbonate solution for heating and degumming to form silk.

[0063] Optionally, the silk cocoon is a silk cocoon after removing the silkworm chrysalis, the shape of the silk cocoon is rectangular or square, and the area of ​​the silk cocoon can be 1mm2 to 1000mm2.

[0064] Optionally, the concentration of the sodium carbonate solution is 20 g / L to 80 g / L, and the volume ratio of the mass of the silkworm cocoons to the sodium carbonate solution is (1:2) g / L.

[0065] Optionally, in step S1011, the sodium carbonate solution is heated by an electric furnace or a pressure cooker, the heating temperature is 60°C to 100°C, the heating pressure is 0.5MPa to 1MPa, and the heating degumming time, that is, the degumming time mentioned above, is 10 minutes to 60 minutes. Optionally, the average molecular weight of the silk fibroin in the silk can be controlled by the heating degumming time. The average molecular weight of the silk fibroin in the embodiment of the present application is 10KDa to 300KDa.

[0066] The above paragraph mentioned that the average molecular weight of silk fibroin in silk can be controlled by the heating degumming time. Specifically, because the shorter the degumming time, the longer the retained molecular weight, and the longer the degumming time, the shorter the retained molecular weight. After research, the degumming time is about 60 minutes, the degree to which the molecules can be recrystallized is the largest, and the mechanical modulus is also the largest. Mechanical curve research found that if the degumming time is less than 60 minutes, the mechanical toughness of the material will be better, and the material can have better elasticity after being subjected to external force, which is conducive to the subsequent mechanical crushing of the material to form a more stable powder structure. After the degumming time is greater than 60 minutes, the material loses its mechanical toughness, and making a gel will also make the material become like a non-sticky sandy texture, which is not conducive to the subsequent stabilization process, and the compactness of the powder will also decrease. Therefore, the early degumming time will also affect the density of the silk protein powder formed subsequently. Based on this, the embodiment of the present application can control the degumming time to 10 minutes to 60 minutes, so as to prepare for the subsequent obtaining of a powder with a larger molecular weight, stronger stability and higher density.

[0067] In the embodiment of the present application, washing silk can remove visible impurities and Na+ in the cocoon, dialysis can remove lithium salts, and centrifugation can remove impurities in silk. The average molecular weight of silk fibroin is mainly changed by heating the silk, and then the corresponding properties are adjusted. The larger the average molecular weight of silk fibroin, the stronger the toughness of the material.

[0068] In step S1013, the silk is placed in ultrapure water and washed multiple times.

[0069] In an embodiment of the present application, in step S1013, the silk is washed by stirring washing or static soaking, wherein the stirring method of the stirring washing is mechanical stirring or magnetic stirring, and the magnetic stirring speed is 1 r / min to 2000 r / min.

[0070] In a single washing process, the mass ratio of silk to ultrapure water is 1:20 to 1:50, and the washing time is 60 seconds to 5 hours. After each washing, the silk is taken out and squeezed dry. The washing can be repeated 1 to 50 times to ensure the cleanliness of the silk.

[0071] In step S1015, the washed silk is dried, and the dried silk is stirred and mixed with a lithium salt aqueous solution to be uniformly mixed and kept warm to obtain a silk fibroin lithium salt aqueous solution.

[0072] In the embodiment of the present application, in step S1015, the drying method of the drying treatment is natural air drying or heating ventilation drying, the temperature of the heating ventilation drying is 5°C to 100°C, and the drying time is 1h to 100h.

[0073] In an embodiment of the present application, in step S1015, the lithium salt aqueous solution is a lithium thiocyanate LiSCN solution or a lithium bromide LiBr solution, the concentration of the lithium salt aqueous solution is 0.01 g / ml to 2 g / ml, and the volume ratio of the mass of the dried silk to the lithium salt aqueous solution is (1 to 100): 100 g / ml; the insulation temperature is 30°C to 50°C, and the insulation time is 0.5h to 5h.

[0074] In step S1017, the silk fibroin lithium salt aqueous solution is poured into a dialysis bag and dialyzed in ultrapure water.

[0075] In the embodiment of the present application, in step S1017, the specification of the dialysis bag is 10Da~10000000Da, and the dialysis method is static dialysis or magnetic stirring dialysis, wherein the stirring speed of the magnetic stirring dialysis is 1r / min~2000r / min.

[0076] Optionally, water can be continuously changed during the dialysis process to speed up the dialysis rate. The time interval for changing water during the dialysis process is 0.1h to 100h, and the volume of ultrapure water required for each dialysis is 1mL to 1000L.

[0077] In step S1019, the dialyzed silk fibroin lithium salt aqueous solution is transferred to a centrifuge tube, centrifuged, and the supernatant after centrifugation is collected to obtain the silk fibroin aqueous solution.

[0078] In the embodiment of the present application, in step S1019, the rotation speed of the centrifugal treatment is 10 r / min to 20000 r / min, the time is 6 s to 2 h, and the temperature is 1° C. to 5° C.

[0079] In step S103, the silk fibroin aqueous solution is placed in a -30°C to -5°C environment and frozen.

[0080] In the embodiment of the present application, after the silk fibroin aqueous solution is prepared, the silk fibroin aqueous solution can be placed in an environment of -30°C to -5°C for freezing.

[0081] In step S105, the frozen silk fibroin aqueous solution is placed in a freeze dryer for vacuum freezing treatment to obtain silk fibroin freeze-dried foam; wherein the vacuum freezing time is 5h to 8h, the vacuum freezing temperature is -20°C to -5°C, and the vacuum freezing pressure is 0.005mBar to 0.8mBar.

[0082] In the embodiment of the present application, the frozen silk fibroin aqueous solution can be placed in a freeze dryer for vacuum freezing treatment to obtain a silk fibroin freeze-dried foam.

[0083] Optionally, the air freezing time is 5h to 8h, the vacuum freezing temperature is -20°C to -5°C, and the vacuum freezing pressure is 0.005mBar to 0.8mBar, so that the standby silk fibroin freeze-dried foam can be obtained.

[0084] In step S20, hexafluoroisopropanol solution is used to dissolve the freeze-dried silk fibroin foam to generate a first solution; in the first solution, the concentration of the silk fibroin is 20%-30%.

[0085] In some feasible embodiments, between the above steps S10 and S20, the above method further includes the step of doping the silk fibroin freeze-dried foam with solid-phase reinforcement particles. The solid-phase reinforcement particles include at least one of ceramic powder, metal powder, and polymer. Accordingly, when the silk fibroin freeze-dried foam is dissolved, the ratio of the total mass of the silk fibroin freeze-dried foam and the solid-phase reinforcement particles to the first preset mass is: 1: (1-10).

[0086] In some feasible embodiments, between the above steps S1 and S2, the above method further includes the step of preparing a composite material corresponding to the freeze-dried silk fibroin foam. Specifically, the freeze-dried silk fibroin foam is added to the calcium phosphate composite powder containing calcium sulfate, mixed evenly, and a solid phase system is obtained. The solidifying liquid containing Na+ is added to the solid phase system, blended into a uniform paste, and a composite material is obtained after solidification treatment. Among them, the weight ratio of the calcium sulfate contained in the calcium phosphate composite powder to the weight ratio of the freeze-dried silk fibroin foam is in the range of 2 to 4, and the solidifying liquid containing Na+ may include but is not limited to: Na2HPO4, NaH2PO4 and NaOH solution. The calcium phosphate composite powder containing calcium sulfate may be a calcium phosphate bone cement-based composite powder containing calcium sulfate. Accordingly, when the freeze-dried silk fibroin foam is dissolved, the total mass of the freeze-dried silk fibroin foam and the calcium phosphate composite powder containing calcium sulfate (i.e., the composite material) is 1: (1 to 10) to the first preset mass. Since the prepared composite material is hydroxyapatite similar to the bone composition of the human body. The composite material can be self-cured in an in vitro environment and then implanted into the body. As a bone repair implant material, the composite material not only has good toughness and biocompatibility, but also improves the pore structure of calcium phosphate bone cement, making it closer to artificial bone.

[0087] In an embodiment of the present application, in step S20, i.e., using hexafluoroisopropanol solution to dissolve the freeze-dried silk fibroin foam to generate the first solution, the mass ratio of the freeze-dried silk fibroin powder to the hexafluoroisopropanol solution is 1:(1-10), the dissolution temperature is 30°C-50°C, the dissolution time is 1h-5h, and the container is sealed during the dissolution to prevent the hexafluoroisopropanol solution from volatilizing. The sealed container can be a sealed glass bottle with a lid, a sealed syringe, or a beaker sealed with a polymer film, etc.

[0088] In the embodiment of the present application, hexafluoroisopropanol is an organic compound with good solubility and stability. Optionally, the concentration of silk fibroin in the first solution is 20%-30%.

[0089] Compared with using an aqueous solution to dissolve the freeze-dried silk fibroin foam, the concentration of the obtained silk fibroin aqueous solution is about 10%. In the embodiment of the present application, the hexafluoroisopropanol solution is used to dissolve the freeze-dried silk fibroin foam, which can dissolve more freeze-dried silk fibroin foam, thereby making the concentration of silk fibroin in the first solution higher. This provides a good preliminary guarantee for obtaining higher density silk fibroin particles in the subsequent preparation.

[0090] In step S30, the first solution and pure water are mixed in a first ratio and left to stand for a first period of time to form a first silk fibroin gel.

[0091] See also Figure 4 , Figure 4 : is a schematic flow chart of a method for preparing a first silk fibroin gel provided in an embodiment of the present application, and the method may include the following steps:

[0092] In step S301, a first volume of a first solution is obtained;

[0093] In step S303, the second volume of pure water is slowly added to the first volume of the first solution for a preset number of additions, and the two solutions are stirred evenly to obtain a mixed solution, in which the first ratio of the first solution to pure water is 5:(1-2).

[0094] In step S305, the mixed solution is statically incubated for a first period of time until the silk fibroin gel is formed to obtain a first silk fibroin gel, wherein the first period of time is 24 hours.

[0095] In the embodiment of the present application, the more water is added, the faster the gelation speed is. If the first ratio of the first solution to pure water in the mixed solution is 5:1, the mixed solution can be statically incubated for 24 hours until the silk fibroin gel is formed to obtain the first silk fibroin gel. If the first ratio of the first solution to pure water in the mixed solution is 5:2, the mixed solution can be statically incubated for about 4 hours until the silk fibroin gel is formed to obtain the first silk fibroin gel. However, the more water is added, the less silk fibroin components therein are after gelation, and then the mechanical properties of the gel are weaker, showing a more brittle nature.

[0096] In step S40, the first silk fibroin gel is placed in a deionized solution at a first temperature, and the hexafluoroisopropanol in the first silk fibroin gel is removed by the deionized solution to obtain a second silk fibroin gel.

[0097] In an embodiment of the present application, in step S40, the first silk fibroin gel is placed in a deionized solution at a first temperature, and the hexafluoroisopropanol in the first silk fibroin gel is replaced and removed by the deionized solution to obtain the second silk fibroin gel. The first temperature is 30°C to 80°C, and the removal time is 3 to 7 days.

[0098] In some possible embodiments, the first silk fibroin gel can be placed in a deionized solution at a first temperature, such as 70 degrees Celsius, and the hexafluoroisopropanol in the first silk fibroin gel can be removed using the deionized solution for 3 days to obtain the final second silk fibroin gel.

[0099] In some possible embodiments, the first silk fibroin gel can be placed in a first sub-temperature, such as a deionized solution at 30 degrees Celsius, and the hexafluoroisopropanol in the first silk fibroin gel can be removed by using the deionized solution for 1 day. Then, it can be placed in a second sub-temperature, such as a deionized solution at 40 degrees Celsius, and the hexafluoroisopropanol in the deionized solution can be removed for 2 days. Then, it can be placed in a third sub-temperature, such as a deionized solution at 60 degrees Celsius, and the hexafluoroisopropanol in the deionized solution can be removed for 3 days to obtain the final second silk fibroin gel.

[0100] That is, the water can be changed 5-10 times in the middle, and the water temperature can be different.

[0101] In step S50, the second silk fibroin gel is broken into a silk fibroin emulsion by using water, and the silk fibroin emulsion is freeze-dried to obtain silk fibroin dry powder particles; the density of the silk fibroin dry powder particles is greater than the density of water.

[0102] In the embodiment of the present application, the deionized solution can be an aqueous solution, a physiological saline solution, etc., and the hexafluoroisopropanol in the first silk fibroin gel is replaced and removed by the deionized solution to obtain a second silk fibroin gel that can be a gel with 100% silk fibroin content.

[0103] The first silk fibroin gel is in a gel state at the molecular level and has relatively weak elasticity. We need to increase the content of its β-folded structure. By heating it in an aqueous solution, we can further increase the content of its β-folded structure. Therefore, its mechanical properties will be further enhanced. That is, the obtained 100% silk fibroin gel will be harder and more conducive to subsequent mechanical crushing.

[0104] In step S50, the second silk fibroin gel is broken into a silk fibroin emulsion by using water, and the silk fibroin emulsion is freeze-dried to obtain silk fibroin dry powder particles, wherein the density of the silk fibroin dry powder particles is greater than the density of water.

[0105] In the embodiment of the present application, the lyophilized silk protein dry powder particles have different sizes. Optionally, the lyophilized silk protein dry powder particles can be sieved using a filter of a preset size to obtain lyophilized silk protein dry powder particles less than or equal to a preset size. Optionally, the preset size is less than or equal to 100 microns.

[0106] Optionally, the density of the silk protein dry powder particles is 1.1 g / cm 3 . Figure 5 Schematic diagram of the density of a silk protein dry powder particle provided in the embodiment of the present application, such as Figure 5 As shown, the silk protein dry powder particles mentioned above are placed in water. After standing for 1-2 minutes, the silk protein dry powder particles sink to the bottom of the water. After being shaken again, they can return to emulsion, indicating that they have not formed a gel.

[0107] Optionally, there may be a plurality of filter screens of different sizes, such as filter screens with apertures of 100 microns, 50 microns, and 20 microns. First, all the silk protein dry powder particles can be sieved through a 100-micron filter screen to obtain silk protein dry powder particles with a size of 100 microns and below, then, a 50-micron filter screen is used to sieve the silk protein dry powder particles of 100 microns and below, and the silk protein dry powder particles of 50 microns and below are distinguished, and then, a 20-micron filter screen is used to sieve the silk protein dry powder particles of 50 microns and below, and the silk protein dry powder particles of 20 microns and above and below 50 microns are distinguished.

[0108] In summary, the silk protein double network hydrogel and the preparation method thereof provided by the present invention have the following technical effects:

[0109] (1) The present invention uses silk fibroin as the main material of the filler, which not only reduces the addition of organic solvents in the production process, making the operation simple and the ingredients safe, but also protein, as a natural polymer material, has a high affinity to the human body and can be naturally absorbed by the human body, thereby greatly reducing the chance of inflammation and infection after surgery and improving the safety of surgery.

[0110] (2) Compared with most existing methods for preparing silk fibroin materials (directly gelling the silk fibroin aqueous solution), the present invention first prepares the silk fibroin aqueous solution into freeze-dried powder, thereby reducing the possibility of hydrogen bonds between water molecules and silk fibroin molecules, which is manifested as a reduction in the intermolecular β-folding structure and an increase in the intramolecular β-folding structure, thereby enhancing the mechanical strength of the silk fibroin material itself.

[0111] (3) Compared with other reported methods for preparing silk protein powder / microparticles (such as spray drying), this method can obtain high-density silk protein microparticles (density greater than water, close to the density of silk protein hard bone nails). Microparticles prepared by other methods have lower density. The advantage is that powders of the same size of particles can be degraded in the body for a longer period of time as fillers, thereby reducing the cost of use.

[0112] (4) Compared with other common solvents, the hexafluoroisopropanol in the present invention has a higher solubility for silk fibroin, and when dissolving silk fibroin, the hexafluoroisopropanol will not destroy the structure of the silk fibroin; the hexafluoroisopropanol solution is used to dissolve the lyophilized silk fibroin powder to generate a silk fibroin fluoroalcohol solution. After the obtained silk fibroin fluoroalcohol solution forms a gel, the hexafluoroisopropanol of the deionized solution is replaced by hexafluoroisopropanol, which can further increase the content of its β-folding structure, so that its mechanical properties will be further enhanced, that is, the obtained 100% silk fibroin gel will be harder and more conducive to subsequent mechanical crushing.

[0113] (5) By setting up heating to displace hexafluoroisopropanol in the process, on the one hand, the displacement is accelerated, and on the other hand, the formation of β-folded structure is promoted. Silk protein with high content of β-folded structure has a longer degradation cycle in vivo, which further increases the degradation cycle of silk protein powder in vivo.

[0114] (6) The silk protein dry powder particles prepared by the present invention are composed of 100% silk fibroin, and the degradation products are amino acids and polypeptides, which can be absorbed as nutrients for human tissue regeneration. The method is conducive to mass production of high-density silk protein powder, which is conducive to large-scale production and has broad application prospects in tissue repair and replacement.

[0115] The embodiment of the present application also provides a silk protein dry powder particle, which is prepared by the above-mentioned preparation method.

[0116] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

[0117] It should be noted that the above-mentioned sequence of the embodiments of the present application is for description only and does not represent the advantages and disadvantages of the embodiments. The above-mentioned specific embodiments of this specification are described. Other embodiments are within the scope of the attached claims. In some cases, the actions or steps recorded in the claims can be performed in an order different from that in the embodiments and still achieve the desired results. In addition, the processes depicted in the drawings do not necessarily require the specific order or continuous order shown to achieve the desired results. In some embodiments, multitasking and parallel processing are also possible or may be advantageous.

[0118] Each embodiment in this specification is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the device embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.

[0119] A person skilled in the art will understand that all or part of the steps to implement the above embodiments may be accomplished by hardware or by instructing related hardware through a program, and the program may be stored in a computer-readable storage medium, and the above-mentioned storage medium may be a read-only memory, a disk or an optical disk, etc.

[0120] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing silk protein dry powder particles, characterized in that: The method comprises the following steps: Preparing a freeze-dried silk fibroin foam; the freeze-dried silk fibroin foam is obtained by degumming silk from silkworm cocoons; the degumming time is 10 minutes to 60 minutes; Dissolving the freeze-dried silk fibroin foam with a hexafluoroisopropanol solution to generate a first solution; in the first solution, the concentration of the silk fibroin is 20%-30%; Mixing the first solution and pure water in a first ratio, and allowing the mixture to stand for a first period of time to form a first silk fibroin gel; placing the first silk fibroin gel in a deionized solution at a first temperature, and removing hexafluoroisopropanol in the first silk fibroin gel by using the deionized solution to obtain a second silk fibroin gel; The second silk fibroin gel is broken into a silk fibroin emulsion by using water, and the silk fibroin emulsion is freeze-dried to obtain silk fibroin dry powder particles; the density of the silk fibroin dry powder particles is greater than the density of water.

2. The method for preparing the silk protein dry powder particles according to claim 1, characterized in that: The method for preparing the freeze-dried silk fibroin foam comprises: preparing a silk fibroin aqueous solution; Freezing the silk fibroin aqueous solution in an environment of -30°C to -5°C; placing the frozen silk fibroin aqueous solution in a freeze dryer for vacuum freezing treatment to obtain the silk fibroin freeze-dried foam; The vacuum freezing time is 5h to 8h, the vacuum freezing temperature is -20°C to -5°C, and the vacuum freezing pressure is 0.005mBar to 0.8mBar.

3. The method for preparing the silk protein dry powder particles according to claim 2, characterized in that: The method for preparing the silk fibroin aqueous solution comprises: Weighing dry and clean silk cocoons, placing them in a sodium carbonate solution, and performing a heating treatment to remove the sericin from the silk cocoons and perform degumming to form silk; placing the silk in ultrapure water and washing it multiple times; The washed silk is dried, and the dried silk is mixed with a lithium salt aqueous solution by stirring and evenly mixing, and the mixture is kept warm to obtain a silk fibroin lithium salt aqueous solution; Pour the silk fibroin lithium salt aqueous solution into a dialysis bag and dialyze in ultrapure water; The dialyzed silk fibroin lithium salt aqueous solution is transferred to a centrifuge tube, centrifuged, and the supernatant after centrifugation is collected to obtain the silk fibroin aqueous solution.

4. The method for preparing the silk protein dry powder particles according to claim 3, characterized in that: The silk cocoon is a silk cocoon after the silkworm pupae are removed; the shape of the silk cocoon is rectangular or square, and the area of ​​the silk cocoon is 1mm2~1000mm2; the concentration of the sodium carbonate solution is 20g / L~80g / L, and the volume ratio of the mass of the silk cocoon to the sodium carbonate solution is (1:2)g / L.

5. The method for preparing the silk protein dry powder particles according to claim 3, characterized in that: The sodium carbonate solution is heated by an electric furnace or a pressure cooker, the heating temperature is 60°C to 100°C, the heating pressure is 0.5MPa to 1MPa, the average molecular weight of the silk fibroin in the silk is controlled by the heating time, and the average molecular weight of the silk fibroin is 10KDa to 300KDa.

6. The method for preparing the silk protein dry powder particles according to claim 3, characterized in that: The silk is washed by stirring washing or static soaking, wherein the stirring method of stirring washing is mechanical stirring or magnetic stirring, and the magnetic stirring speed is 1r / min to 2000r / min; during a single washing process, the mass ratio of the silk to the ultrapure water is 1:20 to 1:50, and the time is 60s to 5h; after each washing, the silk is taken out and squeezed dry, and the washing is repeated 1 to 50 times.

7. The method for preparing the silk protein dry powder particles according to claim 3, characterized in that: The drying method of the drying treatment is natural air drying or heating ventilation drying, the temperature of the heating ventilation drying is 5° C. to 100° C., and the drying time is 1 hour to 100 hours.

8. The method for preparing silk protein dry powder particles according to claim 3, characterized in that: The lithium salt aqueous solution is a lithium thiocyanate solution or a lithium bromide solution, the concentration of the lithium salt aqueous solution is 0.01 g / ml to 2 g / ml, the volume ratio of the mass of the dried silk to the lithium salt aqueous solution is (1 to 100): 100 g / ml; the insulation temperature is 30° C. to 50° C., and the insulation time is 0.5 h to 5 h.

9. The method for preparing the silk protein dry powder particles according to claim 3, characterized in that: The specification of the dialysis bag is 10Da~10000000Da, and the dialysis method is static dialysis or magnetic stirring dialysis; wherein, the stirring speed of the magnetic stirring dialysis is 1r / min~2000r / min, the time interval for changing water during the dialysis process is 0.1h~100h, and the volume of ultrapure water required for each dialysis is 1mL~1000L.

10. The method for preparing silk protein dry powder particles according to claim 3, characterized in that: The rotation speed of the centrifugal treatment is 10 r / min to 20000 r / min, the time is 6 s to 2 h, and the temperature is 1° C. to 5° C.

11. The method for preparing silk protein dry powder particles according to claim 1, characterized in that: The mass ratio of the silk fibroin freeze-dried powder to the hexafluoroisopropanol solution is 1:(1-10), the dissolution temperature is 30°C-50°C, the dissolution time is 1h-5h, and the container is sealed during the dissolution.

12. The method for preparing silk protein dry powder particles according to claim 1, characterized in that: The first ratio is 5:(1-2); the first duration is 24 hours.

13. The method for preparing silk protein dry powder particles according to claim 1, characterized in that: The first temperature is 30° C. to 80° C., and the removal time is 3 days to 7 days.

14. The method for preparing the silk protein dry powder particles according to any one of claims 1 to 13, characterized in that: After freeze-drying the silk fibroin emulsion to obtain silk fibroin dry powder particles, the method further comprises: Using a filter screen of a preset size to sieve the silk protein dry powder particles to obtain silk protein dry powder particles less than or equal to the preset size; The preset size is less than or equal to 100 microns.

15. The method for preparing the silk protein dry powder particles according to any one of claims 1 to 13, characterized in that: The density of the silk protein dry powder particles is 1.1 g / cm 3 .

16. A silk protein dry powder particle, characterized in that: The silk protein dry powder particles are prepared by the preparation method according to any one of claims 1 to 15.